2009
DOI: 10.1111/j.1600-0781.2009.00405.x
|View full text |Cite
|
Sign up to set email alerts
|

Pinpoint papular polymorphous light eruption in Asian skin: a variant in darker‐skinned individuals

Abstract: Our data suggest that pinpoint papular PMLE is not uncommon in darker-skinned individuals in our cohort.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 7 publications
1
9
0
1
Order By: Relevance
“…[3][4][5] In other studies, biopsies were reported to show spongiotic and lichenoid change. [1,[3][4][5][6][7][8][9][10] We found predominantly three patterns: spongiotic (43.7%), lichenoid (22.5%), psoriasiform (18.7%) and we also noted perivascular pattern in 4 (5%) specimens. The common denominator appeared to be the filling and expansion of the papillae in the dermis with inflammatory infiltrate and edema.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…[3][4][5] In other studies, biopsies were reported to show spongiotic and lichenoid change. [1,[3][4][5][6][7][8][9][10] We found predominantly three patterns: spongiotic (43.7%), lichenoid (22.5%), psoriasiform (18.7%) and we also noted perivascular pattern in 4 (5%) specimens. The common denominator appeared to be the filling and expansion of the papillae in the dermis with inflammatory infiltrate and edema.…”
Section: Discussionmentioning
confidence: 93%
“…[1,[3][4][5][6][7][8][9] There is general agreement across studies on the distinctive clinical features of the disease: light to skin colored tiny papules, discrete and coalescing, on photo-exposed skin of the neck and upper limbs, usually sparing the face and occurring more commonly in women except in the Singaporean study where the eruption was common on the face and neck, and more common in men. [8] In contrast, the classic form of polymorphous light eruption, commonly affects the face and dorsa of the hands along with the other sun-exposed areas. [12,13] Furthermore, the clinical morphology is so distinct in our patients that we may lose its value if an umbrella term of polymorphous light eruption (PMLE) is used for this subsets of patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This variant was initially described in Indian and Japanese literature, characterized by 1–2 mm vesicles to erythematous papules on photoexposed body surfaces in skin phototypes IV–VI (Fig. b) . Areas of involvement predominantly include the upper extremities, head and neck and less commonly the face due to natural hardening .…”
Section: Immune‐mediated Photodermatosesmentioning
confidence: 96%